Chitosan intercalated bentonite as natural adsorbent matrix for water-soluble sappanwood dye - Ampa Jimtaisong (2019)
© 2019 Chitosan-bentonite clay composite was prepared for use as adsorbent matrix of water-soluble natural dyes. The addition of chitosan resulted in a relatively rough texture of the composite compared with bentonite. XRD analysis showed that a basal d 001 -space value of the composite (15.545 Å) is higher than that of bentonite clay (14.525 Å) which indicates that chitosan was intercalated into the layer of clay. FT-IR and SEM measurement also suggested that new compound was formed. Water soluble dye extracted from sappanwood was adsorbed onto chitosan-bentonite clay composite at 81.5% adsorption capacity. The dye-adsorbed composite showed different color shade at different pH values. The color stability was investigated under sunlight, fluorescent light, 45 °C, ambient temperature and dark condition for 4 weeks, and the color change of the sappanwood dye-adsorbed composite is less than that of the unadsorbed sappanwood powder in all conditions. The composite greatly improved the color stability of sappanwood dye about five time in the extent. The results of this work showed high potential of the chitosan-bentonite clay composite to be employed as adsorbent matrix for water soluble dyes and help increasing the color stability thus wider its use in industry.